Indoor and peridomestic transmission of American cutaneous leishmaniasis in northwestern Argentina: a retrospective case-control study. - Yadon, Z; Rodrigues, L; Davies, C; Quigley, M (2003)
A case-control study was carried out during 1990-1994 to identify risk factors associated with American cutaneous leishmaniasis (ACL) in Santiago del Estero, Argentina. The study subjects consisted of 171 cases and 308 controls matched by age, sex, and place of residence. The analysis was performed by conditional logistic regression. Risk factors found to be significantly associated with ACL were related to indoor transmission (few rooms in the house, dirt floor, and a permanent opening in lieu of a window); peridomestic transmission (presence of a pond or woodland within 150 m of the house and an agricultural area within 200 m of the house); and human behavior (sleeping in the backyard, collecting water, bathing, and performing agricultural activities). Most transmission appears to have occurred indoors and in the peridomicile. These environments should be included in further research and control policies.